2002
DOI: 10.1002/ijc.10630
|View full text |Cite
|
Sign up to set email alerts
|

Elevated protein expression of cyclin D1 and Fra‐1 but decreased expression of c‐Myc in human colorectal adenocarcinomas overexpressing β‐catenin

Abstract: Mutations of the adenomatous polyposis coli tumor suppressor gene, or its downstream target ␤-catenin, have been implicated in the initiation of most sporadic human colorectal epithelial neoplasms. These mutations, in turn, lead to aberrant nuclear accumulation of ␤-catenin and subsequent activation of the ␤-catenin/Tcf transcription factor complex. In vitro studies utilizing cultured human colon cancer cell lines have identified c-myc, cyclin D1 and fra-1 as target genes of ␤-catenin/Tcf signaling. In our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…Thus, lack of immunoreactivity in tumor cells in the presence of positive staining in non-neoplastic cells would indicate the presence of gene mutations. 13,14 Our study demonstrates a significant lower frequency of negative immunostaining for adenomatous polyposis coli in small intestinal adenocarcinoma than in colorectal adenocarcinoma (31 vs 71%). However, this frequency appears to be somewhat higher than those reported by others using genetic or molecular approaches.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, lack of immunoreactivity in tumor cells in the presence of positive staining in non-neoplastic cells would indicate the presence of gene mutations. 13,14 Our study demonstrates a significant lower frequency of negative immunostaining for adenomatous polyposis coli in small intestinal adenocarcinoma than in colorectal adenocarcinoma (31 vs 71%). However, this frequency appears to be somewhat higher than those reported by others using genetic or molecular approaches.…”
Section: Discussionmentioning
confidence: 55%
“…AP-1 has been implicated in the pathogenesis of cancer in various tissues and plays a critical role in tumor promotion (25,(33)(34)(35). Increased expression of c-Jun has been reported in human colorectal carcinoma (36). A previous study revealed the role of AP-1 in the proliferation of the colon cancer HT29 cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…There are four signal transduction pathways described by Potter [3,4] to be involved in the oncogenesis of hereditary CRC: APC-β-catenin-TCF-myc (Wnt) pathway [5] , microsatellite unstable pathway [6] , p53 pathway and estrogen receptor hypermethylation pathway. However, the signal transduction pathways involved in sporadic CRC remain unclear.…”
Section: Discussionmentioning
confidence: 99%